2012
DOI: 10.1128/aac.05938-11
|View full text |Cite
|
Sign up to set email alerts
|

An Antibiotic That Inhibits a Late Step in Wall Teichoic Acid Biosynthesis Induces the Cell Wall Stress Stimulon in Staphylococcus aureus

Abstract: ABSTRACTWall teichoic acids (WTAs) are phosphate-rich, sugar-based polymers attached to the cell walls of most Gram-positive bacteria. InStaphylococcus aureus, these anionic polymers regulate cell division, protect cells from osmotic stress, mediate host colonization, and mask enzymatically susceptible peptidoglycan bonds. Although WTAs are not re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 72 publications
(92 reference statements)
6
91
0
Order By: Relevance
“…These observations suggest a blocking in cell division. Campbell et al [18] reported similar effects for S. aureus cells treated with targocil, an antibiotic that induces cell wall stress by inhibiting a late step in wall teichoic acid synthesis. Blocking of this biosynthetic pathway is lethal for bacterial cells and this could explain the rapid bactericidal effect induced by alcohol fraction in 1 h of treatment.…”
Section: Cw Pm S a B C Dmentioning
confidence: 57%
“…These observations suggest a blocking in cell division. Campbell et al [18] reported similar effects for S. aureus cells treated with targocil, an antibiotic that induces cell wall stress by inhibiting a late step in wall teichoic acid synthesis. Blocking of this biosynthetic pathway is lethal for bacterial cells and this could explain the rapid bactericidal effect induced by alcohol fraction in 1 h of treatment.…”
Section: Cw Pm S a B C Dmentioning
confidence: 57%
“…To determine whether these compounds act directly on the cell wall synthetic pathway, we measured the effect of the bis-indoles and netropsin on a strain of S. aureus carrying a reporter construct that produces a bioluminescent signal in response to inhibitors of cell wall synthesis. The reporter construct consists of the promoter of vraX, which is induced by inhibitors of cell wall and teichoic acid synthesis and is part of the cell wall stress stimulon [CWSS] (15,16,38), that has been fused to a bacterial luciferase operon (luxABCDE) carried on plasmid (pAmi-vraX). As shown in Fig.…”
Section: As It Was Too Weak) These Values Indi-mentioning
confidence: 99%
“…In line with this, the inhibition of WTA synthesis by deletion of LytR-CpsA-Psr proteins has been shown to increase the basal expression of the 'cell wall stress stimulon', a collection of genes responsible for mounting a general cell wall stress-response in the presence of cell wall damaging-agents (Dengler et al, 2012). The recently discovered antibiotic targocil, which blocks expression of tagG, has also been shown to induce cell wall stress in S. aureus (Campbell et al, 2012). It is plausible that in the hyper-biofilm mutants identified in the present study, the transposon insertions reduce WTA biosynthesis, thereby stimulating a more profound cell wall stress-response in the presence of bile.…”
Section: Discussionmentioning
confidence: 76%